1997
DOI: 10.1046/j.1365-3083.1997.d01-374.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Detrimental Humoral Immune Responses to HIV‐1 in AIDS Patients with CD4 Lymphocyte Counts Less Than 400/mm3

Abstract: The humoral immune response to human immunodeficiency virus type 1 (HIV‐1) was studied in 25 AIDS patients with CD4 lymphocyte counts of less than 400/mm3. Humoral immune responses against tissue culture adapted strains of HIV‐1, and two limited‐passage patient isolates were investigated. Total anti‐HIV antibody levels were not significantly different between different individuals. Neutralizing titres against HIVLAI and HIVSF2 were 10‐ to 100‐fold higher than against clinical isolates. The complement‐mediated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
2
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
4
2
0
Order By: Relevance
“…Our present novel findings, together with those reported previously by our group and others [27][28][29], thus indicate that C-ADE may markedly influence the natural course of HIV disease. This assumption is in disagreement with the results of Montefiori et al [36], who did not find any correlation between C-ADEmediating antibodies and clinical progression.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our present novel findings, together with those reported previously by our group and others [27][28][29], thus indicate that C-ADE may markedly influence the natural course of HIV disease. This assumption is in disagreement with the results of Montefiori et al [36], who did not find any correlation between C-ADEmediating antibodies and clinical progression.…”
Section: Discussionsupporting
confidence: 88%
“…We have measured C-ADE with a markedly higher frequency and in higher amounts in the sera of patients with advanced stage HIV disease compared with those in the sera of asymptomatic HIV-infected persons [27]. These findings were recently confirmed by McDougall et al [28]. In a more recent study [29], we have demonstrated the appearance of high-titre C-ADE to predict the rapid decline of the CD4 cell counts and an increased probability of the development of AIDS.…”
Section: Introductionsupporting
confidence: 68%
“…Similarly, neutralizing MAbs do not mediate infection enhancement and vice versa (44). Complement alone or in the presence of antibodies, however, may cause increased levels of adhesion of the virions to target cells via complement receptors and may thus abrogate the neutralizing effect of sera, as reported here and by McDougall et al (25). It is noteworthy that epitopes for the IEAs have been mapped to the N-terminal two-thirds of the extracellular part of gp41 (36), whereas the NAs recognize epitopes mainly in the variable and CD4 binding domains of the viral envelope proteins of HIV-1 (13, 33a, 34, 35, 39).…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, when the T value is 1, many of the Env spikes on a virion are dispensable for infectivity, allowing a high level of defectiveness. Functionally defective HIV-1 Env proteins, including shed gp120 and the gp41 remnants of subunit dissociation, have been suggested to act as decoy antigens that promote nonneutralizing antibody responses (57,69,87). Low requirements for viral glycoproteins on the retrovirus surface allow the envelope to be densely populated with cellular adhesion molecules, which can facilitate virus-cell attachment in a process that is invisible to the host immune system (34,71,93,98).…”
Section: Discussionmentioning
confidence: 99%